Generating positive self-descriptions in a research context: a discursive psychological and conversation analysis of interview products and practices - Widdicombe, Sue (Qualitative research in psychology, 2025)
Interview research has been criticised because analysts often focus on interviewees' talk and overlook the interviewer's role in its production. This study uses conversation (CA) and discursive psychological (DP) analysis to examine interviews with Syrian and UK participants. It asks what conclusions can be drawn about their positive self-descriptions when analysis attends simultaneously to the sequences of turns and practices within and through which they are generated. The analysis identifies four discursive strategies used to manage inferential difficulties of self-praise: shifting to subject-side assessments; formulating a 'licence to tell'; using third-party reports; and warranting claims. It also shows how self-descriptions were co-produced through question reformulation, continuers and closing sequences. Comparison with studies of spontaneous self-praise shows how modesty is a common concern which is addressed strategically using shared and distinct discursive resources. The paper concludes that the approach developed here can address a key challenge of using interviews for research.